Changing Stony Coral Tissue Loss Disease Dynamics Through Time in Montastraea cavernosa - Aeby, Greta; Ushijima, Blake; Bartels, Erich; Walter, Cory; Kuehl, Joseph; Jones, Scott; Paul, Valerie J. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) is affecting corals across the Western Atlantic and displays species-specific and regional differences in prevalence, incidence, degree of mortality and lesion morphology. We examined two Florida sites with different temporal histories of disease emergence; Fort Lauderdale where SCTLD is endemic and the Lower Florida Keys where SCTLD has recently emerged. Our objectives were to 1) assess the potential impact of SCTLD on overall reef condition by surveying reefs in each region, 2) in a single common species, Montastraea cavernosa, examine differences in SCTLD prevalence, colony mortality, and lesion morphology in each region, and 3) look for differences in contagion by conducting transmission experiments using lesions from each region. Reef surveys found sites in both regions had low coral cover, high algae cover and similar coral species composition. SCTLD prevalence was higher in the Lower Keys than at Fort Lauderdale and two of the common species, M. cavernosa and S. siderea at Fort Lauderdale were dominated by smaller colonies (<5 cm) whereas larger colonies occurred in the Lower Keys. Tagged M. cavernosa SCTLD-affected colonies were followed for two years at one site in each region. In both years, Fort Lauderdale colonies showed declining disease prevalence, low colony mortality, and disease lesions were mainly bleached spots lacking tissue loss. In contrast, Lower Keys colonies tagged in the first year maintained 100% disease prevalence with high mortality, and disease lesions were predominantly tissue loss with no bleached edges. However, SCTLD dynamics changed, with year two tagged colonies showing declining disease prevalence, low mortality, and lesion morphology switched to a mixture of bleached polyps and tissue loss with or without bleached edges. Lesion morphology on colonies was a significant predictor of amount of tissue loss. Aquaria studies found the rate of SCTLD transmission using lesions from the different zones (emergent and endemic) were similar. Our study highlights that differences in coral mortality from SCTLD are not necessarily linked to host species, lesion morphology is reflective of subsequent rate of mortality, and disease dynamics change through time on reefs where the disease has newly emerged.